1998
DOI: 10.1074/jbc.273.45.29360
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Δ5-Desaturase from Mortierella alpina by Heterologous Expression in Bakers' Yeast and Canola

Abstract: A DNA fragment with homology to ⌬6-desaturases from borage and cyanobacteria was isolated after polymerase chain reaction amplification of Mortierella alpina cDNA with oligonucleotide primers corresponding to the conserved regions of known ⌬6-desaturase genes. This fragment was used as a probe to isolate a cDNA clone with an open reading frame encoding 446 amino acids from a M. alpina library. Expression of this open reading frame from an inducible promoter in Saccharomyces cerevisiae in the presence of variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
105
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(108 citation statements)
references
References 33 publications
3
105
0
Order By: Relevance
“…In clade C, a functionally characterized Δ5 Fad from the oleaginous fungus, Mortierella alpina , was found (Michaelson, Lazarus, Griffiths, Napier, & Stobart, 1998). The fatty acid profile of M. alpina has been found to have high levels of ARA and also EPA when conditions are optimal, but lack > C 20 PUFAs, such as DHA (Knutzon et al., 1998; Michaelson et al., 1998). Furthermore, M. alpina has been shown to encode an additional Δ6 desaturase enzyme; however, this sequence is not present in the Swiss‐prot database and therefore was not included in this analysis (Knutzon et al., 1998; Michaelson et al., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In clade C, a functionally characterized Δ5 Fad from the oleaginous fungus, Mortierella alpina , was found (Michaelson, Lazarus, Griffiths, Napier, & Stobart, 1998). The fatty acid profile of M. alpina has been found to have high levels of ARA and also EPA when conditions are optimal, but lack > C 20 PUFAs, such as DHA (Knutzon et al., 1998; Michaelson et al., 1998). Furthermore, M. alpina has been shown to encode an additional Δ6 desaturase enzyme; however, this sequence is not present in the Swiss‐prot database and therefore was not included in this analysis (Knutzon et al., 1998; Michaelson et al., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Related Δ 5 -desaturases are known from plants, fungi, and humans, however the primary structure of JamB is distinct from each of these. The third His box domain in JamB aligns with the Δ 5 -/Δ 6 -desaturases, where the consensus sequence is QXXHH [224]. The functional significance of variations in this signature domain is not known.…”
Section: Jamaicamides-jamaicamidesmentioning
confidence: 99%
“…1. Although the two desaturases (⌬ 6 -and ⌬ 5 -fatty acid desaturases) required for this pathway have been cloned recently from a number of different sources (7)(8)(9)(10)(11)(12)(13)(14), no genes have been characterized for the C2 elongation of the C18 PUFA. Biochemical characterization of mammalian elongation systems (most notably from liver microsomes) has indicated that the ''elongase'' actually consists of four enzyme activities, being made up of a condensing enzyme, a ␤-ketoreductase, a dehydrase, and an enoyl reductase (reviewed in ref.…”
mentioning
confidence: 99%